Assessment of technolog ical quality for sugar beet hybrids (Beta vulgaris L.) by the content of α-amin nitrogen - Я. А. Мельник; М. О. Корнєєва (Plant Varieties Studying and Protection)
The article offers results of genetic value assessment for pollinators resulted from population of high-productive and sugary specialization of Uladivska breeding, to be used for their recurrent improvement and development of hybridization components valuable for combining in creation of synthetics and MS hybrids of sugar beet containing reduced amount of nitrogen α-amin ions.